Does change in neurotransmitter brain status affect the growth of transplantable melanoma? - O. I. Kit; E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; E. I. Surikova; L. K. Trepitaki; N. D. Cheryarina; I. M. Kotieva (Бюллетень сибирской медицины)
Aim. Studying the influence of the features of aminergic brain status on the development of B16/F10 melanoma in mice with urokinase gene knockout and chronic neurogenic pain (CNP).Material and methods. The study included female (n = 68) С57ВL/6 mice with the normal urokinase gene (+uPA) and C57BL/6-PlautmI.IBug-This Plau6FDhu/GFDhu mice with urokinase gene knockout (–uPA). The model of CNP was created in the animals, and in 14 days B16/F10 melanoma was transplanted. The mice were euthanized 21 days after the transplantation. Levels of adrenaline (A), noradrenaline (NA), dopamine (DA), histamine (H), serotonin (5HT), 5-hydroxyindoleacetic acid (5HIAA) were determined in the brain using standard ELISA test systems (Cusabio, China).Results. CNP in (+uPA) females resulted in the reduction of almost all studied biogenic amines (BA). On the opposite, (–uPA) females showed an increase in NA, DA, 5HT and a decrease of H. 5HIAA increased in both CNP and gene knockout. 5HT in (+uPA) females with CNP decreased, while its physiological level in gene knockout mice was maintained. After 3 weeks of tumor growth in animals with CNP, (+uPA) mice demonstrated increased levels of studied BA (except for 5HIAA) compared to mice with CNP alone. Only H increase was observed in (–uPA) mice from the similar group.Conclusion. CNP in mice inhibited A-, NA-, H- and 5HT-ergic systems of the brain; the opposite effects were registered in urokinase gene knockout, except for the H-ergic system. Combination of CNP and melanoma in (+uPA) female mice activated all studied BA systems, and in (–uPA) females – H-ergic system only. Different stressful effects, CNP, and genetic disorders (urokinase gene knockout) contributed to changes in the brain BA system functions, leading to the activation of pro- or antitumor mechanisms.